Motivations as the Key Factor to Exercise Adherence Among Adults with Hypertension - Tjahjono, Cholid Tri; Mayangsari, Veny; Arthamin, Maimun Zulhaidah; Insanitaqwa, Aleyda Z. (British Journal of Healthcare and Medical Research, 2025)
Aim: Regular exercise is a cornerstone of hypertensive treatment, yet many individuals struggle to maintain consistent exercise routines. Motivation plays a crucial role in fostering sustained engagement in health-promoting behaviors, including exercise. This literature review explores the multifaceted nature of motivation associated to exercise adherence, with a particular emphasis on hypertensive individuals. Result: Motivation is a key factor influencing exercise adherence among individuals with hypertension. The motivators and barriers to exercise adherence can be classified into three principal factors: intrapersonal, interpersonal, and environmental, according to the socioecological model. The motivational aspect of intrapersonal factors including as self-efficacy, responsibility to one’s self, enjoyment, health beliefs, baseline physical activity, cognitive factors, knowledge, vicarious experience, socioeconomic income, sociodemographic factors, and appearance. Interpersonal factor, such as patient-healthcare providers relationship and social support, can either facilitate or hinder exercise adherence. Environmental factors can motivate exercise if there are supportive health care system, available health infrastructure, and suitable setting of exercise. Interventions to enhance motivation are essential for increasing exercise adherence and improving health outcomes. Increased social interaction, building strong social support, establishing of good therapeutic rapport, health education, cognitive-behavioral intervention, and strategies to enhance self-efficacy are several approaches to increase motivation. Moreover, motivational interviewing can be applied by the healthcare providers as a counseling approach to elicit behavior change by resolving patient ambivalence and sustaining long-term motivation for exercise adherence. Conclusion: Existing literature indicates a robust association between motivation and exercise adherence in individuals with hypertension. While certain motivational strategies have demonstrated potential, further research is needed to facilitate long-term behavior change and alleviate the burden of hypertension at both individual and population levels.